Optimized placement of parasitic vibration energy harvesters for autonomous structural health monitoring. (July 2020) - Pearson, Matthew; Featherston, Carol A; Pullin, Rhys; Holford, Karen M
Energy harvesting, based on sources including vibration and thermal gradients, has been exploited in recent years to power telemetry, small devices, or to charge batteries or capacitors. Generating the higher levels of power which have thus far been required to run sensor systems such as those needed for structural health monitoring has been more challenging. In addition, harvesters such as those required to capture vibration often require additional elements (e.g. cantilevers) to be added to the structure and harvest over a relatively narrow band of frequencies. In aerospace applications, where weight is at a premium and vibrations occur over a broader range of frequencies, this is non-ideal. With the advent of new, lower power monitoring systems, the potential for energy harvesting to be utilized is significantly increased. This article optimizes the placement of a set of parasitic piezoelectric patches to harvest over the broad band of frequencies found in an aircraft wing and validates the results experimentally. Results are compared with the requirements of a low-power structural health monitoring system, with a closing of the gap between the energy generated and that required being demonstrated.